A Liberal Peace Analysis of the UN Peacekeeping Operations in the DRC - Charles Nyuykonge (African Journal of Political Science)
Since its inception in May 1948, the United Nations (UN) peacekeeping operation has evolved through a series of changes in the international security environment to becoming the world’s most formidable multi-national instrument for international security intervention for peace and security. Its operation in the Democratic Republic of the Congo (DRC) is one of the largest operations in the history of UN peacekeeping operations in Africa. Yet, it has been one of the most controversial missions given the fact that the DRC remains mired in relative instability despite decades of the blue-helmet intervention in the country, particularly since the start of MONUC in 1999. UN efforts at ending insecurity and restoring political order in the country have seen a succession of peacekeeping mandates and operational orientations thus informing changing theoretical perspective among scholars. Notable, there is what is perceived as a transition from Liberal Peace to Sustaining Peace operational models and the adoption of these as analytical frames. Despite this tendency towards theoretical bifurcation in the body of academic literature purporting transformation in the context and content of the UN DRC operations, the UN systems’ operational framing reflects more of a continuum than transformation in the guiding framework of action. This paper is conceived to examine the theoretical and operational frames in the discourse of UN mission in the DRC, and their validity in the analyses of UN peacekeeping missions in the DRC. The paper’s adopted qualitative discourse approach finds significant differences in the conceptual parameters for evaluating progress in UN missions and suggests that these gaps be bridged by reconciling theory and practice in contexts such as in the DRC in a changing global security environment.